Pengaruh Orientasi Politik terhadap Partisipasi Perempuan Muda pada PILPRES 2024 (Studi Empiris terhadap Pilihan Politik Mahasiswi Fakultas Bahasa dan Seni Unimed) - Manotar Leryaldo Sinaga; Mima Defliyanti Saragih; Joy Novi Yanti Lumbantobing; Talita Sembiring; Muthi’ah Lathifa; Kania Nova Ramadhani; Al Firman Simangunsong (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research is entitled The Influence of Political Orientation on Young Women's Participation in the 2024 Presidential Election (Empirical Study of the Political Choices of FBS Unimed Students). With the aim of analyzing the factors that influence political orientation towards the political participation of young women, especially FBS Unimed students in the 2024 Presidential Election (Pilpres). Political orientation, which includes individual political beliefs, values, and attitudes, has a significant role in determining the level of political participation of young women. The method used in this research is descriptive qualitative. It is a research method that describes a condition or situation and events systematically. Data collection is in the form of interviews involving female students of FBS Unimed as respondents. the results showed that there is a significant and complex positive relationship between political orientation and political participation of young women.